On the Occasion of World Hypertension Day 2016 - Hamid Nasri (مجله دانشکده پزشکی اصفهان, 2016)
The World Hypertension Day celebrates 17th of May of every year by concentrating on an important global health subject. For World Hypertension Day (WHD) 2014, they have chosen “Know your Blood Pressure “as the theme. Chronic kidney disease is a worldwide public health puzzle and hypertension is one the most important cause of damage to the kidneys. In fact by improved screening, diagnostic efforts and judicious use of antihypertensive using renoprotective agents, we will continue to reduce the incidence of strokes, heart failure and also heart attacks, hence our patients will be capable of enjoying their health.